Impact of ornithine phenylacetate (OCR-002) in lowering plasma ammonia after upper gastrointestinal bleeding in cirrhotic patients. (November 2016) - Ventura-Cots, Meritxell; Concepción, Mar; Arranz, José Antonio; Simón-Talero, Macarena; Torrens, Maria; Blanco-Grau, Albert; Fuentes, Inma; Suñé, Pilar; Alvarado-Tapias, Edilmar; Gely, Cristina; Roman, Eva; Mínguez, Beatriz; et al.
Background: Ornithine phenylacetate (OP) has been proven effective in lowering ammonia plasma levels in animals, and to be well tolerated in cirrhotic patients. A trial to assess OP efficacy in lowering plasma ammonia levels versus placebo in cirrhotic patients after an upper gastrointestinal bleeding was performed. The primary outcome was a decrease in venous plasma ammonia at 24 hours. Methods: A total of 38 consecutive cirrhotic patients were enrolled within 24 hours of an upper gastrointestinal bleed. Patients were randomized (1:1) to receive OP (10 g/day) or glucosaline for 5 days. Results: The primary outcome was not achieved. A progressive decrease in ammonia was observed in both groups, being slightly greater in the OP group, with significant differences only at 120 hours. The subanalysis according to Child–Pugh score showed a statistically significant ammonia decrease in Child–Pugh C-treated patients at 36 hours, as well as in the time-normalized area under the curve (TN-AUC) 0–120 hours in the OP group [40.16 μmol/l (37.7–42.6); median (interquartile range) (IQR)] versus placebo group [65.5 μmol/l (54–126); p = 0.036]. A decrease in plasma glutamine levels was observed in the treated group compared with the placebo group, and was associated with the appearance of phenylacetylglutamine in urine. Adverse-event frequency was similar in both groups. No differences in hepatic encephalopathy incidence were observed. Conclusions: OP failed to significantly decrease plasma ammonia at the given doses (10 g/day). Higher doses of OP might be required in Child–Pugh A and B patients. OP appeared well tolerated.